Determinants of Adolescents’ Knowledge of Sexuality: A Cross-Sectional Study among Students of Syarif Hidayatullah State Islamic University Jakarta - Rahmah Hida Nurrizka; Moh. Irvan; Siti Rahmah Hidayatullah Lubis; Fajaria Nurcandra (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Background: Sexual knowledge is essential for adolescents as it plays a role in increasing their awareness of reproductive health, preventing unintended pregnancies, and reducing the risk of sexually transmitted infections (STIs). However, data show that 85% of adolescents in Indonesia aged 12–17 still lack adequate knowledge about sexuality. The aim of this study was to analyse the determinants related to adolescents' understanding of sexuality. Method: This research was a cross-sectional survey with a sample size of 319 students at UIN Syarif Hidayatullah Jakarta. The sampling was conducted using a multistage sampling technique across 12 faculties. The inclusion criteria for this study were active students in good health, while the exclusion criteria were students who were unwilling to participate. The research was conducted from January to November 2023. Result: The research shows that many students still do not know well about gender stereotypes (51.1%), the difference between primary and secondary signs of puberty (90.3%), and sexual relations (58.9%). The dominant variable influencing students' knowledge of sexuality was whether they had discussed reproductive health (p-value=0.021; OR=2.139; 95% CI 1.119-4.809). Conclusion: Adolescents’ knowledge of sexuality was generally quite good. However, their understanding remains low in several key aspects, such as gender differences, physical and emotional changes during puberty, and the misconception that first-time sexual intercourse cannot lead to pregnancy. This highlights the need for more comprehensive education to enhance adolescents’ understanding of various aspects of sexuality.